Association of admission hyperglycemia and all-cause mortality in acute myocardial infarction with percutaneous coronary intervention: A dose–response meta-analysis - Cheng, Shao-Yong; Wang, Hao; Lin, Shi-Hua; Wen, Jin-Hui; Ma, Ling-Ling; Dai, Xiao-Ce (Frontiers in Cardiovascular Medicine, 2022)
Objective The aim of this study is to evaluate the associations between admission hyperglycemia and the risk of all-cause mortality in patients with acute myocardial infarction (AMI) with or without diabetes, to find optimal admission glucose intervention cut-offs, and to clarify the shape of the dose–response relations. Methods Medline/PubMed and EMBASE were searched from inception to 1 April 2022. Cohort studies reporting estimates of all-cause mortality risk in patients with admission hyperglycemia with AMI were included. The outcomes of interest include mortality and major adverse cardiac events (MACEs). A random effect dose–response meta-analysis was conducted to access linear trend estimations. A one-stage linear mixed effect meta-analysis was used for estimating dose–response curves. Relative risks and 95% confidence intervals were pooled using a random-effects model. Results Of 1,222 studies screened, 47 full texts were fully reviewed for eligibility. The final analyses consisted of 23 cohort studies with 47,177 participants. In short-term follow-up, admission hyperglycemia was associated with an increased risk of all-cause mortality (relative risk: 3.12, 95% confidence interval 2.42–4.02) and MACEs (2.34, 1.77–3.09). In long-term follow-up, admission hyperglycemia was associated with an increased risk of all-cause mortality (1.97, 1.61–2.41) and MACEs (1.95, 1.21–3.14). A linear dose–response association was found between admission hyperglycemia and the risk of all-cause mortality in patients with or without diabetes. Conclusion Admission hyperglycemia was significantly associated with higher all-cause mortality risk and rates of MACEs. However, the association between admission hyperglycemia and long-term mortality risk needs to be determined with caution. Compared with current guidelines recommendations, a lower intervention cut-off and more stringent targets for admission hyperglycemia may be appropriate. Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022317280], identifier [CRD42022317280].